Pediatric Hypertension: Parent Perspectives - Assim M. AlAbdulKader MD, MPH; Erica F. Morse MA; Matthew F. Daley MD; Goutham Rao MD (SAGE Publishing, 2020)
Clinical practice guidelines for diagnosis and management of pediatric hypertension have been available for decades. Yet, most cases of hypertension in children are undiagnosed. Provider and system-based factors, such as the complexity of diagnostic standards, and a failure among physicians to recognize the importance of hypertension in children, play a role in underdiagnosis. It is unclear, however, how patient and family behaviors impact the diagnosis and treatment of pediatric hypertension. We aimed to explore the perspectives of parents whose children have had multiple high blood pressure readings or have been diagnosed with hypertension to inform clinicians with areas for practice improvement. In a 2 site qualitative study, we interviewed parents of 15 children diagnosed with hypertension. Results from semi-structured interviews with parents revealed barriers to the diagnosis of pediatric hypertension, including uncertainty about the diagnosis and concerns around the accuracy of blood pressure measurements. Delay in diagnosis and lack of child engagement emerged as obstacles to the treatment of pediatric hypertension.